ISLAMIZING SMARTPHONES AS A WAY TO PREVENT MORAL DECLINE IN EARLY CHILDHOOD IN THE MODERN ERA - Ramadora, Novriti (SYAHADAT: Journal of Islamic Studies, 2024)
This study reviews the Islamization of smartphones as a prevention of moral decline in children today. Due to globalization and the rapid development of technology, children often spend time with smartphones. This causes children to watch things they shouldn't watch so they follow and bring them into the real world. And many other negative impacts. This study details that by Islamizing and associating smartphones with Islamic things, it will make children's morals better. The method used is a literature study, which observes previous research on the Islamization of science and technology. And regarding the difficulty in Islamization, it is due to the emergence of challenges both from within Islam and from outside Islam.